Characterization of the early molecular changes in the glomeruli of Cd151−/− mice highlights induction of mindin and MMP-10. Issue 1 (December 2017) - Naudin, Crystal; Smith, Brian; Bond, Danielle R.; Dun, Matthew D.; Scott, Rodney; Ashman, Leonie; Weidenhofer, Judith; Roselli, Séverine
Abstract In humans and FVB/N mice, loss of functional tetraspanin CD151 is associated with glomerular disease characterised by early onset proteinuria and ultrastructural thickening and splitting of the glomerular basement membrane (GBM). To gain insight into the molecular mechanisms associated with disease development, we characterised the glomerular gene expression profile at an early stage of disease progression in FVB/NCd151 −/− mice compared toCd151 +/+ controls. This study identified 72 up-regulated and 183 down-regulated genes in FVB/NCd151 −/− compared toCd151 +/+ glomeruli (p < 0.05). Further analysis highlighted induction of the matrix metalloprotease MMP-10 and the extracellular matrix protein mindin (encoded bySpon2 ) in the diseased FVB/NCd151 −/− GBM that did not occur in the C57BL/6 diseased-resistant strain. Interestingly, mindin was also detected in urinary samples of FVB/NCd151 −/− mice, underlining its potential value as a biomarker for glomerular diseases associated with GBM alterations. Gene set enrichment and pathway analysis of the microarray dataset showed enrichment in axon guidance and actin cytoskeleton signalling pathways as well as activation of inflammatory pathways. Given the known function of mindin, its early expression in the diseased GBM could represent a trigger of both further podocyte cytoskeletal changes and inflammation, thereby playing a key role in the mechanisms of disease progression.